2006
DOI: 10.1159/000091508
|View full text |Cite
|
Sign up to set email alerts
|

Size at Birth, Postnatal Growth and Risk of Obesity

Abstract: Epidemiological studies over the last 15 years have shown that size at birth, early postnatal catch-up growth and excess childhood weight gain are associated with an increased risk of adult cardiovascular disease and type 2 diabetes. At the same time, rising rates of obesity and overweight in children, even at pre-school ages, have shifted efforts towards the identification of very early factors that predict risk of subsequent obesity, which may allow early targeted interventions. Overall, higher birth weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(203 citation statements)
references
References 55 publications
8
189
0
6
Order By: Relevance
“…IUGR was associated with higher total cholesterol:HDL-cholesterol ratio compared with not-IUGR (B= 11%; 95% CI 1. [8][9][10][11][12][13][14][15][16][17][18][19][20]. Other non-significant trends for lipid profile (raised triacylglycerol, LDL-cholesterol and total cholesterol) were seen for IUGR (Fig.…”
Section: Effects Of Sga and Iugr On Markers Of The Metabolic Syndromementioning
confidence: 87%
See 1 more Smart Citation
“…IUGR was associated with higher total cholesterol:HDL-cholesterol ratio compared with not-IUGR (B= 11%; 95% CI 1. [8][9][10][11][12][13][14][15][16][17][18][19][20]. Other non-significant trends for lipid profile (raised triacylglycerol, LDL-cholesterol and total cholesterol) were seen for IUGR (Fig.…”
Section: Effects Of Sga and Iugr On Markers Of The Metabolic Syndromementioning
confidence: 87%
“…Small size at birth indicates some period(s) of slow fetal growth, and thus poor intrauterine growth conditions have been suggested to be the cause of the observed impact upon later health. However, there also seems to be an interaction between birthweight (BW) and weight gain during infancy and childhood in determining later health [7][8][9][10]. Identification of particularly critical periods of fetal life, as well as of individuals at particular risk of later disease, could be crucial for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Small babies who undergo early catch-up growth that is characterized by a greater accumulation of fat mass relative to lean body mass have an increased risk of becoming obese in later life compared with those born at higher birth weights. [18][19][20] Early catch-up growth in infants born pre-term, who also have a reduced fat mass at birth, and who were fed formula milk also show increased risk of cardio-metabolic disease in later life, 21,22 including obesity. 23 A number of studies have also shown a greater incidence of obesity in adults who were formula fed as opposed to breast fed during infancy, 23,24 although not all studies found this.…”
Section: The Developmental Origins Of Human Metabolic Diseasementioning
confidence: 99%
“…30 Others have, however, reported that birth weight was inversely associated with central obesity after adjustment for BMI. 31 Further, neither secular changes in the distribution of birth weight, nor secular changes in the association between birth weight and later risk of obesity can explain the increase in the prevalence of obesity among Danish children. 30 Adjustment for sex, preterm birth, parental socioeconomic status, and concurrent breastfeeding did not change the results.…”
Section: Discussionmentioning
confidence: 95%